2022
DOI: 10.1108/ejm-03-2022-0159
|View full text |Cite
|
Sign up to set email alerts
|

Creating discursive channels: generating and disseminating impactful research insights into the strategic sales enablement of retail technology

Abstract: Purpose To meet the complex technology needs of retail clients, technology providers must work in a close partnership with their clients and co-envisage a strategic vision for the role that technology should play in the client’s value chain. However, many providers lack the sales capabilities needed to do this. This study aims to examine the need for providers to transition from transaction-oriented to solution selling-oriented approaches. To do so, this study explores the impact outcomes of a knowledge-exchan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(8 citation statements)
references
References 14 publications
(19 reference statements)
1
6
0
Order By: Relevance
“…However, this study also emphasizes the sociotechnical implications of organizational technology adoption that are critical for successful implementation of a broad range of retail technologies that are directly experienced by consumers, building on previous work that had begun to highlight these key interrelationships (see Berg et al, 2005;Bonetti et al, 2022;Kaarst-Brown and Robey, 1999;Manfreda and Štemberger, 2019;Naicker and Van Der Merwe, 2018). In particular, this study identified how sociotechnical implications are influenced by the contrasting demographics/characteristics and experience with technology of the various actors involved in the adoption decision and implementation processes, building on previous work by Bonetti et al (2022), Manfreda and Štemberger (2019), Montecchi et al (2022), Olsson et al (2019) and Shankar et al (2020), Addressing RQ3, CFIT types, and the related drivers/barriers and reasons, lead to different approaches to CFIT adoption decisions; termed embedded, transformative and opportunistic, (outlined in Table IV), which develops a categorization of sociotechnical implications identified in practitioner literature (e.g. Lawson 2022).…”
Section: Discussionmentioning
confidence: 82%
See 4 more Smart Citations
“…However, this study also emphasizes the sociotechnical implications of organizational technology adoption that are critical for successful implementation of a broad range of retail technologies that are directly experienced by consumers, building on previous work that had begun to highlight these key interrelationships (see Berg et al, 2005;Bonetti et al, 2022;Kaarst-Brown and Robey, 1999;Manfreda and Štemberger, 2019;Naicker and Van Der Merwe, 2018). In particular, this study identified how sociotechnical implications are influenced by the contrasting demographics/characteristics and experience with technology of the various actors involved in the adoption decision and implementation processes, building on previous work by Bonetti et al (2022), Manfreda and Štemberger (2019), Montecchi et al (2022), Olsson et al (2019) and Shankar et al (2020), Addressing RQ3, CFIT types, and the related drivers/barriers and reasons, lead to different approaches to CFIT adoption decisions; termed embedded, transformative and opportunistic, (outlined in Table IV), which develops a categorization of sociotechnical implications identified in practitioner literature (e.g. Lawson 2022).…”
Section: Discussionmentioning
confidence: 82%
“…technology suppliers, business consultants, investment partners) and the inter-organizational relationships across internal and external actors (i.e. alignment amongst actors involved or interaction barriers - Manfreda and Štemberger, 2019;Montecchi et al, 2022); government regulations (e.g. support for organizational R&D, privacy policies, regulations to attract skilled labor); and technology infrastructure support.…”
Section: External Drivers and Barriers To Cfit Adoptionmentioning
confidence: 99%
See 3 more Smart Citations